Sharia Perda; Among Women and Political Identity - Faizah, Nur (Proceedings of Annual Conference for Muslim Scholars, 2019)
Women and identity politics are actual problems and often invite endless long debates. Women are often forgotten in the history of the Indonesian Nation, especially related to policies such as sharia regulations. The birth of Islamic sharia regulations is not from a vacuum, but is born from a very long and twisted process. Regional autonomy has become the main entrance to the emergence of shari'a regulations as a form of regulatory decree both whose authority is attributive (inherent) or delegative (derivative). The rise of the expansion of new regions as a result of regional autonomy policy, apparently also led to the strengthening of identity politics that seemed to be inherent and must be present in every regional policy taken especially in sharia regulations. Women and sharia regulations become interesting phenomena to be studied from various sides, both political, cultural, legal and religious aspects. This paper portrays women and identity politics in shari'a regulations. A review of how women's representation and identity politics influence the contents of shari'a regulations.